Executive interference and the erosion of the rule of law: a comparative study of the prosecution of official corruption offences in Nigeria, South Africa, and the United States of America - Uchegbune, Temple Chinedum (Department of Public Law, 2026)
Executive interference in prosecuting official corruption offences erodes the rule of law, threatening democratic integrity and governance. This thesis examines this erosion in Nigeria, South Africa, and the United States of America through a comparative doctrinal study, analysing how constitutional sociology, political economy, cultural politics, and political cultures shape interference. Three hypotheses guide the research: in Nigeria, centralised control and military-shaped tolerance drive executive interference and undermine prosecutorial independence; in South Africa, state capture and an emergent democratic culture with racial nuances facilitate executive interference and weaken prosecutorial autonomy; and in the United States of America, presidential pardons and increasing executive pressure disrupt accountability and undermine prosecutorial independence. Drawing on statutes, legal texts, case law, and secondary sources, the study reveals distinct interference mechanisms—Nigeria's Attorney General discretion and presidential pardons, South Africa's political pressure and state capture, and the United States of America's presidential pardons and political pressure—fracturing prosecutorial independence, equality and impartiality, thus breaching the promise of resource protection under the social contract. Findings highlight that constitutional design, economic incentives, cultural practices, and societal attitudes drive this interference, leading to the erosion of the rule of law, distrust of government and the depletion of state resources. The absence of robust prosecutorial autonomy exacerbates interference, varying by Nigeria's post-military legacy, South Africa's transitional pluralism, and the United States of America's use of presidential pardons and recent executive overt hostility to the prosecution. Recommendations propose independent prosecutorial bodies, oversight mechanisms, and public accountability measures to strengthen the rule of law, deepen the separation of powers, enhance prosecutorial independence and safeguard the social contract. This study advances the understanding of the multifaceted drivers of executive interference, offering actionable insights to improve democratic governance across diverse contexts.